Examining the integrity behavior challenges of enforcement officers in Malaysian local government - Rasli, Mohd Rezal; Abdul Manaf, Halimah; Ismail, Mazlan (Business Perspectives, 2020)
There is a call from society to examine the integrity behavior challenges of local government (LG) enforcement officers who work directly with citizens due to the nature of this job. One of the job requirements of enforcement officers is to investigate law enforcement directly to their customers, such as petty traders, hawkers, business owners, developers and contractors, and others. In executing their duties, particularly on law enforcement, high integrity behavior and professionalism of enforcement officers in LG administrative areas of responsibility are necessary. Based on the framework, the study aims to examine the integrity behavior challenges of enforcement officers from the citizens’ and staff ’ perspectives, in particular, on to what extent the officers face the difficulties and challenges in executing their enforcement tasks. Thus, during the study, 30 respondents, namely the citizens and LG staff in Kedah, were surveyed. The data were analyzed using thematic analysis to gain specific dimensions related to integrity behavior. From the citizens’ perspective on LG enforcement teams’ integrity behavior, challenges were related to main aspects such as biasness, political intervention, and bureaucracy matters. Meanwhile, LG staff consider integrity behavior challenges to be affected by opportunistic attitudes among staff, workforce, and financial issues. The study suggests that enforcement officers should develop soft skills, employability skills, and upgrade academic levels to understand the current situation and develop negotiation skills to deal with grassroots society.